Experimental investigation on an innovative built-up cold-formed steel I-section connection - Ahmed Shamel Fahmy; Sherine Mostafa Swelem; Khaled Mohamed Khalifa (Alexandria Engineering Journal)
Bolted connections for built-up cold-formed sections are studied using different section configurations, gusset plates, and bolt arrangements. This paper presents the study of a connection between beam and column in light-weight steel frames with spans ranging between 8.0 and 12.0 m and a maximum height of 6.0 m that are used in agricultural sheds. The cross section of the beam and column is a novel built-up cold-formed cross section. A total of eight connections were tested and studied. The purpose of the study is to determine the effect of serval factors on the moment capacity and failure modes of the connection. The experimental study considered the effects of different shapes of tie plates, numbers, and spacings of bolts, as well as the effect of strengthening angles with different numbers of bolts in the connections. The experimental results showed that the failure modes in all connection types were due to a local failure in the connecting parts. The experimental results revealed that the configuration type has a great influence on the moment capacity of the connection.